Beneficial and detrimental effects of processed dietary fibers on intestinal and liver health: health benefits of refined dietary fibers need to be redefined!. (20th January 2020) - Singh, Vishal; Vijay-Kumar, Matam
Abstract: Consumption of processed foods—which are generally composed of nutritionally starved refined ingredients—has increased exponentially worldwide. A rise in public health awareness that low fiber intake is strongly linked to new-age disorders has spurred food manufacturers to fortify processed foods with refined dietary fibers (RDFs). Consumption of whole foods rich in natural fibers undoubtedly confers an array of health benefits. However, it is not clear whether RDFs extracted from the whole plant, kernel, and fruit peels exert similar physiological effects to their naturally occurring counterparts. Recent studies caution that RDFs are not universally beneficial and that inappropriate consumption of RDFs may risk both gastrointestinal and liver health. Herein, we briefly summarize the beneficial and detrimental effects of RDFs on digestive health and discuss the contribution of metabolites derived from microbial fermentation of RDFs in driving such positive or negative health outcomes.